2011
DOI: 10.1161/hypertensionaha.111.171512
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation in the Mechanical and Neural Components of the Baroreflex

Abstract: Abstract-Diminished baroreflex sensitivity in the morning negatively influences morning coronary blood flow and blood pressure control in hypertensive patients. Our aim was to determine the contribution of the mechanical and neural components of the cardiac baroreflex to diurnal variation in blood pressure control. In 12 healthy participants, we used the modified Oxford method to quantify baroreflex sensitivity for rising (G up ) and falling (G down ) pressures in the morning (7:00 AM) and afternoon (4:00 PM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 51 publications
(72 reference statements)
4
34
1
2
Order By: Relevance
“…All of them demonstrated that a reduction of cardiovagal BRS occurred concomitant with BP increase in the morning, and it was suggested that cardiovagal BRS may be one of the determining factors for morning surge (4,33,36). Given the fact that a reduction of cardiovagal BRS and its correlation with morning BP was also observed in healthy normotensive subjects (4,33) and that this relationship disappeared in hypertensive seniors in the current study, cardiovagal BRS may not be a predominant factor for morning BP increase in elderly hypertensive subjects. Indeed, multiple regression analysis showed that the lower cardiovagal BRS tended to be the factor for the higher morning surge in normotensive subjects, but not in elderly hypertensive subjects whose morning surge was significantly impacted by sympathetic BRS.…”
Section: Sympathetic Neural Control Of Blood Pressure In the Morningmentioning
confidence: 99%
See 1 more Smart Citation
“…All of them demonstrated that a reduction of cardiovagal BRS occurred concomitant with BP increase in the morning, and it was suggested that cardiovagal BRS may be one of the determining factors for morning surge (4,33,36). Given the fact that a reduction of cardiovagal BRS and its correlation with morning BP was also observed in healthy normotensive subjects (4,33) and that this relationship disappeared in hypertensive seniors in the current study, cardiovagal BRS may not be a predominant factor for morning BP increase in elderly hypertensive subjects. Indeed, multiple regression analysis showed that the lower cardiovagal BRS tended to be the factor for the higher morning surge in normotensive subjects, but not in elderly hypertensive subjects whose morning surge was significantly impacted by sympathetic BRS.…”
Section: Sympathetic Neural Control Of Blood Pressure In the Morningmentioning
confidence: 99%
“…Cardiovagal baroreflex sensitivity (BRS), which regulates BP at the heart through the autonomic nervous system, was negatively correlated with morning SBP (4). Moreover, it was found that a decreased cardiovagal BRS was caused by a reduction in distensibility of the carotid artery, especially during the BP rise in the morning (33). Therefore, it seems that hypertensive patients with greater arterial stiffness have a lesser ability to buffer against BP increases in the morning.…”
mentioning
confidence: 99%
“…Measurement sessions were done in the morning [23] in a quiet room in the Leiden University Medical Center. Room temperature was kept at 23°C.…”
Section: Measurementsmentioning
confidence: 99%
“…We have shown that 1) the morning rise in blood pressure is related to overall reductions in integrated baroreflex gain, 2) that for falling pressures the lower integrated gain in the morning was caused by reduced neural gain compared with the afternoon, and 3) for rising pressures the lower integrated gain in the morning was caused by reduced mechanical gain compared with the afternoon 25 . These unique findings hold the prospect of guiding the development of future treatment strategies aimed at lowering cardio-and cerebrovascular events that occur more frequently in the morning.…”
Section: Diurnal Variations In Baroreflex Functionmentioning
confidence: 86%
“…However, mathematical modeling procedures can be applied for more objective analysis. For example, a piecewise linear regression can be applied to the raw data points to statistically identify breakpoints that occur at the upper and lower ends of the data set ( Figure 5) 24,25 . Other approaches for the objective identification of cardiac-vagal BRS have been reported in the literature including the use sigmoid 26 , logistic 27 and elliptical functions 28 .…”
Section: The Modified Oxford Methodsmentioning
confidence: 99%